Testing the asymmetric effects of Interest Rates in Botswana: A NARDL Approach to the McKinnon-Shaw hypothesis - Puskas, Princess Refilwe (School of Economics, 2021)
The many relationships among macroeconomic variables tend to follow a nonlinear path despite the more common linear assumptions. Previous research has shown that the speed at which macroeconomic variables fall is often rarely the same as the speed at which they rise, further suggesting the nonlinearity. This paper therefore aims to test the presence and impacts of the asymmetric effects of interest rates on savings, investment and economic growth by employing a Nonlinear Autoregressive Distributed Lag (NARDL) approach to the McKinnonShaw hypothesis in Botswana. More precisely, the study seeks to test the asymmetric effects of interest rates on the level of savings and investment and the impact of financial liberalisation on economic growth. Till date, there is very little empirical research investigating the asymmetric effects of interest rates, and even less research on this relationship in Botswana. The main contribution of this study is to fill in the research gap by analysing data for the period spanning 1995:Q1−2017:Q4. The study finds a positive relationship between real deposit rates and saving rates as well as a negative association between real bank lending rates and investment levels in the short run. Lastly, the financial liberalisation index is positively related to economic growth. These results are in line with the findings that liberalisation of interest rates generates more savings, investment and subsequently growth in the short run. However, the same does not hold for the long run results. It is therefore imperative that authorities formulate long run objectives aimed at setting real deposit rates at competitive levels to boost savings, encourage investment and promote economic growth in Botswana.